DOKLINE (APLIKASI DOKTER ONLINE) BERBASIS ANDROID - Dias Adi Pratomo; Hernanda Eka Putra; Moch Ilham Faza (Jurnal Transformatika, 2017)
of events that can occur in a period of time and place or location so that objective function as closely as possible can be fulfilled. This problem arises in various areas of activity and installation such as hospitals, universities, airlines, factories and others. The design of the problem varies according to the needs and constraints in the field. Doctor Online (Dokline) Android-based applications can be used to find out where and whenever a doctor of any disease that is appropriate and needed by the community is on duty practice. By using a smartphone that uses android operating system and has been installed with this application, then the community is expected to be helped by can access it in realtime.